2016
DOI: 10.1186/s12888-016-0741-9
|View full text |Cite
|
Sign up to set email alerts
|

An integrated workplace mental health intervention in a policing context: Protocol for a cluster randomised control trial

Abstract: BackgroundIn this paper, we present the protocol for a cluster-randomised trial to evaluate the implementation and effectiveness of a workplace mental health intervention in the state-wide police department of the south-eastern Australian state of Victoria. n. The primary aims of the intervention are to improve psychosocial working conditions and mental health literacy, and secondarily to improve mental health and organisational outcomes.Methods/designThe intervention was designed collaboratively with Victoria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
44
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 30 publications
(60 citation statements)
references
References 66 publications
(66 reference statements)
1
44
0
Order By: Relevance
“…A previous RCT of this manager training showed that it resulted in changes to managers’ confidence and reactive behavior that lasted for six months at least [ 22 ]. The second existing face-to-face program, which was more preventative in its approach, aimed to improve psychosocial working conditions within an organization by changing the managers’ behavior to best promote a mentally healthy workplace [ 36 ]; the principles within this program were based on the management competencies for preventing and reducing stress at work developed by the Health and Safety Executive (HSE) in the UK [ 37 ]. HeadCoach was developed by combining the content from these two face-to-face programs and transforming the material into a format compatible with online delivery.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A previous RCT of this manager training showed that it resulted in changes to managers’ confidence and reactive behavior that lasted for six months at least [ 22 ]. The second existing face-to-face program, which was more preventative in its approach, aimed to improve psychosocial working conditions within an organization by changing the managers’ behavior to best promote a mentally healthy workplace [ 36 ]; the principles within this program were based on the management competencies for preventing and reducing stress at work developed by the Health and Safety Executive (HSE) in the UK [ 37 ]. HeadCoach was developed by combining the content from these two face-to-face programs and transforming the material into a format compatible with online delivery.…”
Section: Methodsmentioning
confidence: 99%
“…HeadCoach integrates the components recognized as key to mental health training and aims to build managers’ confidence and ability to best support the mental health needs of the staff they supervise. The content for this online program has been derived from two separate face-to-face programs developed for managers with a focus on the mental health of their employees [ 22 , 32 ], which, when combined, encompass the recommended reactive and preventative components. We acknowledge that e-learning cannot offer some benefits that face-to-face contact with an educator may provide, and discussion with other participants in the course is often limited or not available.…”
Section: Introductionmentioning
confidence: 99%
“…Rates of absenteeism will be measured using employees’ self-report of recent sickness absence, and items from the World Health Organisation HPQ (WHOHPQ) Presenteeism Questionnaire [ 29 ] will be used to measure employees’ work performance. Employees’ perceived level of support from managerial staff will be measured through the Psychosocial Safety Climate Scale [ 30 ] and the manager scales on a workplace social support scale [ 31 , 32 ]. Level of employee work engagement will be measured through a variation of the Utrecht Work Engagement Scale used in previously conducted work engagement surveys [ 33 ].…”
Section: Methodsmentioning
confidence: 99%
“…In another study 64 1.1% in the variance of leisure time physical activity was found in working groups among employees. Therefore, the estimated ICC for the primary outcome in this study was set to 0.01 and cluster size was set to 20 65 . An effect size of the intervention programme for individual physical activity was estimated based on a previous meta-analysis 17 and an cRCT.…”
Section: Methods and Analysismentioning
confidence: 99%